Challenges in the diagnosis and management of gaucher's disease in a young adult libyan arab female - Fawaris, Nada; Esaadi, Mohamed; Tumi, Ali; Elhamedi, Aisha; Al Montasir, Ahmed (Ibnosina Journal of Medicine and Biomedical Sciences, 2021)
Gaucher's disease is a rare lysosomal storage disease that can present with a wide range of clinical symptoms according to type and severity, ranging from mild general wellbeing, organomegaly, pancytopenia, neurological symptoms, lung involvement, and even death, making the diagnosis and work up challenging to reach a diagnosis. We report a Libyan Arab female presented with bruises after minor trauma, bone aches, and fatigue. A 35-year-old female from Libyan–Arab ethnicity attended the hematology clinic complaining of bruises after minor trauma, bone aches, and undue fatigability. She mentioned and evident from her medical record that she has been suffering from these complaints for 5 years and does not have any definite diagnosis. Mild splenomegaly was the only finding on clinical examination this time. There was no fever and no lymphadenopathy. Thrombocytopenia with a platelet count 90 × 10 and quot; 3/ml, and splenomegaly of 16 cm was found on investigations. She was diagnosed with cryptogenic thrombocytopenia, and she was advised for a follow-up visit. Our patient attended a follow-up visit twice in the next 18 months with similar complaints of manageable bruising, bone pain, and fatigability. Hematology reports showed thrombocytopenia in each visit. An ultrasonogram of the abdomen revealed a gallbladder stone and spleen have a size of 17 cm. Bone marrow biopsy was done, and a blood test confirmed glucocerebrosidase enzyme deficiency. Considering the diagnosis of Gaucher's disease, treatment with imiglucerase infusion was started. Unfortunately, she failed to continue the treatment due to a shortage of supply of the medication. A few months later, she got pregnant and developed threatened abortion, which ended with a miscarriage. This case illustrates the need to consider this disease in the differential diagnoses when dealing with unexplained thrombocytopenia, anemia, hepatomegaly, and splenomegaly. There are several challenges in the diagnosis and treatment of Gaucher's disease, particularly in resource-limited settings.
Keywords: Delayed diagnosis; Gaucher's disease; Libya; treatment challenges